Hubungan Kompetensi, Independensi, Akuntabilitas dan Kepatuhan Pada Kode Etik Dengan Kinerja Auditor Pada Inspektorat Provinsi Bengkulu - Akmal, Samsul; Mulyadi, Mulyadi; Fhikri, Rijalul (STIA Bengkulu, 2025)
The purpose of this study was to analyze the correlation between competence, independence, accountability, and compliance with the code of ethics with the auditor performances in Inspectorate of Bengkulu Province. The relationship can be determined by analyzing the correlation between the four variables with the performance of auditors by distributing questionnaires to 15 (fifteen) professional auditor. The analysis method used in this study was Rank Spearman Correlation Test.Partial correlation test results on the four independent variables, it is known that which has the closest correlation with the auditor performances in Inspectorate of Bengkulu Province is accountability, with a value of correlation is 0.691. Furthermore Spearman rank correlation test for all independent variables with the auditor performances showed a correlation coefficient 0.697 with a degree of error (α = 5%) where the count rs > rs table. This means that H0 is rejected and H1 is accepted, so it can be concluded that: there is a real and significant correlation between competence, independence, accountability and compliance with the code of ethics with the auditor performances in Inspectorate of Bengkulu Province.